2011
DOI: 10.1021/jf2005707
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Açaí (Euterpe oleracea Mart.) Pulp on IgE-Mediated Mast Cell Activation

Abstract: The palm fruit açaí is known to have potential health benefits due to its antioxidant scavenging capacities. Pretreatment of IgE-sensitized mouse primary cultured mast cells with açaí pulp resulted in the dramatic suppression of antigen-induced degranulation in a dose-dependent manner. Similarly, açaí suppressed IgE-mediated degranulation and transcription of the cytokine genes from a cultured mast cell line of rat basophilic leukemia (RBL)-2H3 cells. Açaí could selectively inhibit FcεRI signaling pathways. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Its in vitro anti-inflammatory effects have also been demonstrated by other researchers. Pretreatment of IgE-sensitized mouse primary cultured mast cells with açaí pulp showed a dramatic dose-dependent suppression of antigen-induced degranulation, transcription of selective cytokine genes, and inhibition of FcεRI signaling pathways as well as the FcεRI-mediated complementary signaling pathway, suggesting the pulp is a potent inhibitor of IgE-mediated mast cell activation . Açaı́ pulp anthocyanin-rich extracts have been shown to reduce inflammatory stress signaling in BV-2 (hippocampal) mouse microglia .…”
Section: Research Strategies: An Example Using Açaí Fruit Pulpmentioning
confidence: 99%
See 1 more Smart Citation
“…Its in vitro anti-inflammatory effects have also been demonstrated by other researchers. Pretreatment of IgE-sensitized mouse primary cultured mast cells with açaí pulp showed a dramatic dose-dependent suppression of antigen-induced degranulation, transcription of selective cytokine genes, and inhibition of FcεRI signaling pathways as well as the FcεRI-mediated complementary signaling pathway, suggesting the pulp is a potent inhibitor of IgE-mediated mast cell activation . Açaı́ pulp anthocyanin-rich extracts have been shown to reduce inflammatory stress signaling in BV-2 (hippocampal) mouse microglia .…”
Section: Research Strategies: An Example Using Açaí Fruit Pulpmentioning
confidence: 99%
“…Pretreatment of IgE-sensitized mouse primary cultured mast cells with acai ́pulp showed a dramatic dosedependent suppression of antigen-induced degranulation, transcription of selective cytokine genes, and inhibition of FcεRI signaling pathways as well as the FcεRI-mediated complementary signaling pathway, suggesting the pulp is a potent inhibitor of IgE-mediated mast cell activation. 146 Acaı ṕulp anthocyanin-rich extracts have been shown to reduce inflammatory stress signaling in BV-2 (hippocampal) mouse microglia. 147 Results from this study showed that pretreatment of microglia with individual acaı ́pulp fractions was protective against LPS-induced NO release, COX-2 expression, nitrite production, inducible nitrous oxide synthase expression, p38 mitogen-activated protein kinases (p38-MAPK) expression, and TNF-α and NF-κB release.…”
Section: ■ Anti-inflammatory Dietary Components and Their Mechanismsmentioning
confidence: 99%
“…Exposure of IgE-sensitized mouse primary cultured mast cells to EO pulp resulted in suppression of IgE-mediated degranulation and transcription of the cytokine genes from a cultured mast cell line originated from rat basophilic leukemia (RBL-2H3), selectively inhibited FcεRI signaling pathways and suppressed the FcεRI-mediated complementary signaling pathway. In general, EO inhibited IgE-mediated mast cell activation [ 85 ].…”
Section: Biological Eo Activities: Application In the Prevention Amentioning
confidence: 99%
“…The Linus Pauling Institute and the European Food Safety Authority state that dietary anthocyanins and other flavonoids have little or no antioxidant value after digestion. 2 It should be noted that in 2011, Hiriguchi and colleagues 3 found that the properties in the acai berry suppressed the degradation of cellular integrity in mice. In a recent human study of 10 overweight individuals who consumed acai berries for 30 days, lower fasting glucose and insulin levels as well as lower cholesterol levels were found, but there was no effect on blood pressure.…”
Section: The Natural Acai Berrymentioning
confidence: 99%